Locally constant model uncertainty risk measure - Lazar Obradović (Bielefeld University, Center for Mathematical Economics (IMW), 2019)
This paper introduces a (coherent) risk measure that describes the uncertainty of the model (represented by a probability measure P₀) by a set Pᵧ of probability measures each of which has a Radon-Nikodym's derivative (with respect to P₀) that lies within the interval [λ; 1/λ] for some constant λ ϵ (0,1]. Economic considerations are discussed and an explicit representation is obtained that gives a connection to both the expected loss of the financial position and its average value-at-risk. Optimal portfolio analysis is performed - different optimization criteria lead to Merton portfolio. Comparison with related problems reveals examples of extreme sensitivity of optimal portfolios to model parameters and the choice of risk measure.
urn:nbn:de:0070-pub-29337481
Keywords: 330; Risk measure; Model uncertainty; Value at risk; Average value at risk; Optimal portfolio; Merton portfolio